Respuesta :

Answer:

[tex] \boxed{\sf x - 7} [/tex]

Given:

f(x) = - 3x - 5

g(x) = 4x - 2

To Find:

(f + g)(x)

Step-by-step explanation:

[tex] \sf (f + g)(x) = f(x) + g(x) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = - 3x - 5 + 4x - 2 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 4x - 3x - 5 - 2 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = x - 5 - 2 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = x - 7[/tex]

ACCESS MORE